2013
DOI: 10.1088/0004-637x/770/2/132
|View full text |Cite
|
Sign up to set email alerts
|

Large Abundances of Polycyclic Aromatic Hydrocarbons in Titan's Upper Atmosphere

Abstract: In this paper, we analyze the strong unidentified emission near 3.28 μm in Titan's upper daytime atmosphere recently discovered by Dinelli et al. We have studied it by using the NASA Ames PAH IR Spectroscopic Database. The polycyclic aromatic hydrocarbons (PAHs), after absorbing UV solar radiation, are able to emit strongly near 3.3 μm. By using current models for the redistribution of the absorbed UV energy, we have explained the observed spectral feature and have derived the vertical distribution of PAH abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 35 publications
(87 reference statements)
3
102
0
Order By: Relevance
“…36,37 Anions are also known astrochemicals 21,38 making PAH anions a nice marriage of concepts for astrochemical exploration. Lastly, large molecular anions have been surprisingly detected in the atmosphere of Titan, 39,40 but it is currently unclear as to what atoms and shapes may actually compose these molecules. Consequently, improved models as to the electronic states of PAHs and PANHs will help to describe the chemistry of combustion and of interstellar environments with more completeness.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Anions are also known astrochemicals 21,38 making PAH anions a nice marriage of concepts for astrochemical exploration. Lastly, large molecular anions have been surprisingly detected in the atmosphere of Titan, 39,40 but it is currently unclear as to what atoms and shapes may actually compose these molecules. Consequently, improved models as to the electronic states of PAHs and PANHs will help to describe the chemistry of combustion and of interstellar environments with more completeness.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are abundant in regions of our solar system, such as the atmosphere of Titan (López-Puertas et al 2013), and they may be ubiquitous throughout the interstellar medium (ISM; Siebenmorgen et al 2014). PAHs are likely carriers of several spectral features of the ISM (Van der Zwet & Allamandola 1985; Vijh et al 2004), including the unidentified infrared bands (UIRs) between 3 and 20 μm, the range of stretching and bending vibrations of aromatic hydrocarbons (Tielens 2008;Kwok & Zhang 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of alkane (aliphatic) absorption features in the haze spectra between ∼60−500 km is at odds with the analysis of high-altitude (600−1250 km) Cassini/VIMS observations López-Puertas et al 2013), which concluded that there are aromatic compounds in the ionospheric haze. At first glance, it seems also inconsistent with the detection of HCN and NH 3 in the cores of haze particles collected by Huygens/ACP at low altitude (20−130 km) (Israël et al 2005), but it can be argued that the VIMS occultation measurements most likely probe only the outer shell of the particles.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, Dinelli et al (2013) and López-Puertas et al (2013) have attributed a daytime emission feature observed at 3.28 μm in Cassini/VIMS limb spectra to aromatic hydrocarbons contained in the haze at altitudes of 600−1250 km (with a maximum around 950 km). The predominant absorption by heavy alkane ices at ∼60−500 km altitude in the 1−5 μm VIMS solar occultation spectra seems at odds with their results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation